2019
DOI: 10.1177/0972150918824953
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Concentration and Dividend Payout in Emerging Markets: Evidence from India

Abstract: Ownership concentration plays an important role in determining the dividend payout of firms. Ownership concentration of Indian companies is quite high due to their peculiar shareholding pattern. We examine the relationship between ownership concentration and dividend payout in India over the period 2010–2017 using panel-data methodology and found that ownership concentration is positively correlated with dividend payout. The evidence, which is at odds with that in many developed markets, corroborates similar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…The results obtained by the author are consistent with the conclusions by Easterbrook (1984) and Shleifer and Vishny (1997) who argue that in a situation of ownership the principal shareholders require a high level of dividends in order to reduce agency costs. More recently, Anh and Tuan (2019) and Arora and Srivastava (2021) also prove that ownership concentration plays a vital role in the dividend payment policy in the Vietnamese and Indian contexts, respectively. They prove that deciding to pay dividends or not is influenced by the level of ownership concentration structure.…”
Section: Ownership Concentration and Dividend Distribution Policymentioning
confidence: 95%
See 1 more Smart Citation
“…The results obtained by the author are consistent with the conclusions by Easterbrook (1984) and Shleifer and Vishny (1997) who argue that in a situation of ownership the principal shareholders require a high level of dividends in order to reduce agency costs. More recently, Anh and Tuan (2019) and Arora and Srivastava (2021) also prove that ownership concentration plays a vital role in the dividend payment policy in the Vietnamese and Indian contexts, respectively. They prove that deciding to pay dividends or not is influenced by the level of ownership concentration structure.…”
Section: Ownership Concentration and Dividend Distribution Policymentioning
confidence: 95%
“…They prove that deciding to pay dividends or not is influenced by the level of ownership concentration structure. By examining the relationship between ownership concentration and dividend payout in India, Arora and Srivastava (2021) found that ownership concentration is positively correlated with dividend payout. The authors add that the presence of a large shareholder, other than an individual, outside the promoter group has a negative influence on the dividend payout.…”
Section: Ownership Concentration and Dividend Distribution Policymentioning
confidence: 99%
“…Despite not reflecting the relative voting power of shareholders, the HOCI succeeds in capturing the dispersion of ownership across shareholders and the relative power of a group of shareholders (Goergen & Renneboog 2001). High ownership concentration observations are those whose HOCI is above the median value of the index for all companies (Arora & Srivastava 2019). Low ownership concentration observations are those whose HOCI is below the median value of the index for all companies (Arora & Srivastava 2019).…”
Section: Ownership Concentration Dummy Variablesmentioning
confidence: 99%
“…High ownership concentration observations are those whose HOCI is above the median value of the index for all companies (Arora & Srivastava 2019). Low ownership concentration observations are those whose HOCI is below the median value of the index for all companies (Arora & Srivastava 2019). For each companyyear observation, the HOCI was calculated per company as the square of percentage shareholding held by the top five shareholders (Harada & Nguyen 2011).…”
Section: Ownership Concentration Dummy Variablesmentioning
confidence: 99%
“…In empirical studies relating to dividend policy, ownership concentration is measured in terms of the Herfindahl ownership concentration index (HOCI), which is based on the shareholding of the top five shareholders in companies (Gonzalez et al 2017;Harada & Nguyen 2011), as well as the top shareholder category in a company (Truong & Heaney 2007). High ownership concentration companies are those whose Herfindahl index is above the median value of the index for all companies (Arora & Srivastava 2019). Previous South African studies have considered ownership concentration in relation to capital structure, corporate performance and agency costs (Dube 2018;Qopana 2018), with only a limited focus on dividend policy under the previous tax regime prior to the introduction of dividends tax in 2012 (Abor & Fiador 2013;Arko et al 2014).…”
Section: Ownership Concentrationmentioning
confidence: 99%